2021
DOI: 10.3390/rs13193826
|View full text |Cite
|
Sign up to set email alerts
|

ME-Net: A Multi-Scale Erosion Network for Crisp Building Edge Detection from Very High Resolution Remote Sensing Imagery

Abstract: The detection of building edges from very high resolution (VHR) remote sensing imagery is essential to various geo-related applications, including surveying and mapping, urban management, etc. Recently, the rapid development of deep convolutional neural networks (DCNNs) has achieved remarkable progress in edge detection; however, there has always been the problem of edge thickness due to the large receptive field of DCNNs. In this paper, we proposed a multi-scale erosion network (ME-Net) for building edge dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The network selection is very significant because the crisper building edges will directly improve the performance of the building corner extraction and shape vectorization in later steps. We noticed that ME-Net [10] produced relatively crisp and accurate building edges. In Section IV-A, we have demonstrated that ME-Net is more suitable in our hierarchy than the other state-of-the-art edge detection networks.…”
Section: B Me-netmentioning
confidence: 87%
See 4 more Smart Citations
“…The network selection is very significant because the crisper building edges will directly improve the performance of the building corner extraction and shape vectorization in later steps. We noticed that ME-Net [10] produced relatively crisp and accurate building edges. In Section IV-A, we have demonstrated that ME-Net is more suitable in our hierarchy than the other state-of-the-art edge detection networks.…”
Section: B Me-netmentioning
confidence: 87%
“…3: Set the classification threshold to 0.5 for all the pixels in P, and store the edge pixels in B. which are same as the parameters of the published study [10]. Since the ME-Net produced the building edge probability map with values between 0 and 1, we set a threshold [28], [29], [30] for classifying both the edge and nonedge pixels, and the threshold is generally 0.5 [31].…”
Section: B Me-netmentioning
confidence: 99%
See 3 more Smart Citations